ANALISIS PENGGUNAAN TENAGA KERJA PERTANIAN PADA USAHATANI PADI SAWAH (STUDY KASUS DI DESA KARANG DUREN) - Endang Sri Sudalmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2009)
ABSTRACT The aim of this research is to know how vast the used of the workers in farming industries is. This research is to know how (HPK) comes from the internal families and how (HPK) comes from outsider. Beside that it also seeks the information of what segment of works done by both female and male workers. The method used in this research is descriptive approach. The results obtained from this research are:The usage of the workers in farming industry per acre are; Land owner farmer 69,6 HKP, Land leaseholder farmer 77,5 HKP, and farmer employee 65,7 HKP.The usage of internal family workers and outsiders; Land owner farmers who choose to use internal family workers are 15 HKP; land owner farmers who choose to use outsiders are 54,6 HKP; land leaseholder who choose to use internal family workers are 6 HKP; land leaseholder who choose to use outsiders are 71,5 HKP; farmer employee who choose to use internal family workers are 39,6; and on the other hand farmer employee who choose to use outsiders are 33,6 HKP.Farming industry activity done by the female workers is planting, while the male workers carry out the land cultivating and seed spreading. There are also activities can be accomplished by both female and male workers; rice cutting and harvest time. Key words: Farming industry, Rice filed.